Characterization of the acceptable daylight quality in typical residential buildings in Hong Kong. (September 2020) - Wang, Jun; Wei, Minchen; Ruan, Xiukai
Abstract: Characterizing daylight quality for flats in residential buildings is critically important in Hong Kong, where buildings are close to each other. In this study, we performed Climate Based Daylight Modeling (CBDM) calculations on 400 flats in a public housing property using three different methods. In addition to the Typical Meteorological Year (TMY) data, the actual weather data was measured throughout an entire year and used in the CBDM calculations. At the same time, a questionnaire survey was conducted to collect the residents' subjective evaluations on the daylight quality and luminous environment in their flats from a long-term perspective. Based on the 340 completed surveys, it was found that the residents' satisfaction with daylighting had the most significant influence on their satisfaction with overall luminous environment. Two measures—the average sDA300/50% and the maximum average daylight illuminance—were found to be highly correlated to the residents' satisfaction with daylight in their flats. A flat with an average sDA300/50% above 66% and a maximum average daylight illuminance above 5, 624 lx was found to provide acceptable daylight quality for typical residential buildings in Hong Kong. Highlights: Calculating daylight quantity and measures using TMY and actual weather data. Collecting residents' evaluations on daylight quality from a long-term perspective. Correlating subjective evaluations with objective measures focusing a same period of time.